2017
DOI: 10.1104/pp.17.01568
|View full text |Cite
|
Sign up to set email alerts
|

Branched Pectic Galactan in Phloem-Sieve-Element Cell Walls: Implications for Cell Mechanics

Abstract: A major question in plant biology concerns the specification and functional differentiation of cell types. This is in the context of constraints imposed by networks of cell walls that both adhere cells and contribute to the form and function of developing organs. Here, we report the identification of a glycan epitope that is specific to phloem sieve element cell walls in several systems. A monoclonal antibody, designated LM26, binds to the cell wall of phloem sieve elements in stems of Arabidopsis (Arabidopsis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 61 publications
3
58
0
1
Order By: Relevance
“…As recently described by Torode et al , the LM26 branched galactan epitope is specifically detected in phloem sieve elements in several systems. In the case of the strawberry fruit the LM26 epitope was detected in all primary cell walls of ripe fruit albeit at a relatively low level but at an increased level relative to unripe fruit cell walls (Fig.…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations
“…As recently described by Torode et al , the LM26 branched galactan epitope is specifically detected in phloem sieve elements in several systems. In the case of the strawberry fruit the LM26 epitope was detected in all primary cell walls of ripe fruit albeit at a relatively low level but at an increased level relative to unripe fruit cell walls (Fig.…”
Section: Resultssupporting
confidence: 63%
“…The identification and functional significance of these specific sets of vascular cells with the branched galactan epitope is far from clear. Previous studies have demonstrated both phloem sieve element specificity in certain systems and also the widespread distribution of the LM26 epitope in garlic bulb cell walls (Torode et al ). The occurrence of branched galactan has been implicated with a higher elasticity of cell walls (Mikshina et al , Torode et al ).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…AM-AFM has been successful in characterizing biomass (Kirby et al, 1996;Salvadori et al, 2014;Farahi et al, 2017) and in particular the architecture of plant cell walls at the molecular level which in turn is essential in improving lignocellulosic feedstock properties (Zhang et al, 2013b(Zhang et al, , 2017Keplinger et al, 2014;Torode et al, 2018). AM-AFM mapping of cellulose topography revealed the right-handed twisted nature of microfibrils and the periodic distribution of glucose and fiber unit along the microfibrils (Hanley et al, 1997).…”
Section: Amplitude Modulation Afm (Am-afm): Structural Propertiesmentioning
confidence: 99%